Prognostic value of transcriptomic determination of tumour-infiltrating lymphocytes in localised breast cancer. (October 2019) - Truntzer, Caroline; Isambert, Nicolas; Arnould, Laurent; Ladoire, Sylvain; Ghiringhelli, Francois
Abstract: Purpose: Tumour-infiltrating lymphocyte (TIL) detection by histology is associated with outcomes in breast cancer; nevertheless, analysis standardisation is difficult. We determined whether transcriptomic data could generate a genomic signature that estimated TIL infiltrates and determined patient prognosis in localised breast cancer. Experimental design: Using 1928 transcriptomic profiles of pure cells, we generated a genetic signature specific to lymphocyte, myeloid, stromal and cancer cells. We then computed a score based on this signature and tested the association between the score and the TILs estimated for patients in an adjuvant setting from public and private data sets. We tested the capacity of the transcriptomic RNA TIL score to predict disease-free survival (DFS) or overall survival (OS) through multivariate Cox models adjusted for classical clinical variables and PAM50 molecular classification in two public data sets (Carte d'Identité des Tumeurs [CIT], n = 530; Metabric, n = 1832). Results: A high RNA TIL score was significantly associated with the presence of a high level of TILs as assessed by histology. The score was also associated with DFS and OS in multivariate Cox models adjusted for molecular and clinical variables (CIT: OS hazard ratio [HR] = 0.15 [0.04, 0.61], p-value = 0.007; DFS: 0.27 [0.08, 0.8] p-value = 0.02; Metabric: OS HR = 0.87 [0.77, 0.97], p-value = 0.01). The association between the RNA TIL score and survival was tested by univariate analysis in each molecular subgroup; the RNA TIL score was associated with survival only in basal-like tumours. Conclusions: Determination of the TIL rate using a transcriptomic signature is feasible and has a high prognostic value in patients with basal-like tumours in an adjuvant setting. Highlights: Immune gene signatures address clinical questions in early breast cancer. Development of a RNA TIL score based on gene expression in an adjuvant setting. RNA TIL score highlights greater TIL accumulation in basal and HER2 tumors. RNA TIL score is prognostic in both basal-like and HER2 tumors. Simple tool to better determine prognosis in early breast cancer patients.